88.4k views
2 votes
What is the solution to the equation 1 + 3x = -13 + 5x? Convert your answer to a decimal, if necessary.

User Arsalan T
by
5.3k points

2 Answers

4 votes

Answer:

Explanation:

1 + 3x = 5x - 13

-2x + 1 = -13

-2x = -14

x = 7

User Scorchio
by
5.6k points
3 votes

Answer:

x=7

Explanation:


1 + 3x = - 13 + 5x

Collect like terms and simplify


3x - 5x = - 13 - 1 \\ - 2x = - 14

Divide both sides of the equation by -2


( - 2x)/( - 2) = ( - 14)/( - 2)

Simplify


x = 7

User Pradeep Pati
by
5.4k points